2015
DOI: 10.1007/s10886-015-0548-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Passive Chemical Camouflage in the Parasitic Mite Varroa destructor

Abstract: -Social insect colonies provide a stable and safe environment for their 34 members. Despite colonies been heavily guarded, parasites have evolved numerous 35 strategies to invade and inhabit these hostile places. Two common strategies are chemical 36 mimicry via biosynthesis of the hosts' odour or chemical camouflage were compounds 37 are acquired straight from the host. The ectoparasitic mite Varroa destructor feeds on the 38 heamolymph of its honeybee host Apis mellifera and uses chemical mimicry to remain 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…This agrees with the previous findings that mites were more similar to their immediate host's developmental stage [6,7,11], but our study used different host species to challenge the mite's ability to modify its HC. Because mites clustered according to their new hosts, but not according to their original hosts, we assumed that these mites changed their HC profiles after being transferred to the new host.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with the previous findings that mites were more similar to their immediate host's developmental stage [6,7,11], but our study used different host species to challenge the mite's ability to modify its HC. Because mites clustered according to their new hosts, but not according to their original hosts, we assumed that these mites changed their HC profiles after being transferred to the new host.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study [7] showed that mites are not actively mimicking their hosts, instead by passively using host materials via contact. Our data here suggest that, at least for mites from Ac, some active processes might be involved because they mimicked their hosts better.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that our focal mites and foraging bees were both from the same colony does mean that this study neglects possible effects of chemical adaptation between the mites and bees. Varroa mites have been shown to passively absorb the cuticular hydrocarbon profile of their host hive [25,26]. Therefore, a forager might have had an easier time detecting and removing a mite if the mite had the hydrocarbon profile of a foreign colony, (though mite grooming-avoidance behavior suggests increased detectability may not be sufficient to stop infestation.)…”
Section: Discussionmentioning
confidence: 99%
“…Since mites prefer to use nurse bees as hosts over foragers [30,31,32], perhaps movement to these non-feeding refugia provides a safe place for a mite to wait until the forager it has infested brushes past a nurse bee in the hive. Kather and colleagues have shown that mites entering a new colony require a period of at least three hours to chemically adapt to the odors of their new hosts, [26] which offers another explanation for why mites on flowers would initially move to non-feeding sites which offer refuge from host grooming.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior suggests that the renewal or the restoration of the cuticle chemical profile by the spider is not regulated via biosynthesis, but by continuous exogenous transfer, indicating the use of chemical camouflage to remain in the hosting colony (Dettner & Liepert, 1994). When the Varroa destructor Anderson and Trueman, 2000 mite was experimentally introduced in one colony of a different host bee species (Apis cerana Fabricius, 1793), it acquired a chemical profile similar to the new hosting species demonstrating chemical camouflage of the parasite mite (Kather et al, 2015). In fact, no case of chemical mimicry by biosynthesis has been attributed to the myrmecophilous spiders, and the integration with the ant colonies occurs by the contact with the nest material, contact with the workers or by the predation of larvae and pupae (Cushing, 2012), yet some cuticular hydrocarbon studies are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%